Organisasi Pembelajaran, Kompetensi Dan Kinerja Karyawan Bank BRI Di Jakarta - Thea H. Rahardjo (Jurnal Ekonomi, 2016)
His study aimed to determine empirically the retail mix in small business retail, which includes Physical Facilities Merchandising, pricing, promotion, services and Organization/Personal, as a predictor of the performance of small retail businesses and competitive advantage. The method used in sampling was purposive sampling, a total of 280 respondents drawn at small retail businesses in Tangerang. The data analysis technique used is Structural Equation Modeling (SEM), using LISREL version 8.8 are needed to test the hypothesis. The results showed, retail mix small business strategy that includes Physical Facilities Merchandising, services and Organization/Personal can be used to predict the performance of retail, which means that the research hypothesis tested. While pricing, promotion can not be used to predict the performance of retail. Furthermore, the retail business performance can be used to predict the competitive advantage. These results can be material for the attention of small retail businesses to keep improving the combination of the retail mix, either already affect or not affect the performance of the business, because good performance can affect the competitive advantage for retailers in running the business.